An internationalist national Islamic struggle? Narratives of 'brothers abroad' in the discursive practices of the Islamic Party of Malaysia (PAS) - Mueller, Dominik M. (South East Asia Research, 2010)
Localized constructions of transnational Islamic kinship or 'brothers abroad' are an integral part of discursive practices within the community of the Islamic Party of Malaysia (PAS). Based on empirical data gained from anthropological fieldwork between 2009 and 2010, this article examines domestic manifestations and the implicit subtexts of the party's foreign policy, with particular regard to the Palestinian cause. Narratives of victimization and heroism are thereby as important as demonizing projections of delinquency and evil, while at times images of local and external enemies melt together. Furthermore, it is shown that PAS's Islamist internationalism is essentially (g)local, whereas national and ummahist identities are referred to only selectively.
Created from Fastlane, Scopus look-up
Keywords: Islamist politics; Localization; Malaysia; PAS; Transformative adaptations; Transnational Islam

Besprechung: Ulrich Pfister (u.a.) Kulturen des Entscheidens. Narrative - Praktiken - Ressourcen. - Müller, Dominik (Archiv für Kulturgeschichte : AKG, 2021)

Beyond the Sharia State: Public Celebrations and Everyday State-Making in the Malay Islamic Monarchy of Brunei Darussalam - Müller, Dominik (Asian Journal of Law and Society, 2022)
This article describes post-colonial state-making in the absolute monarchy of Brunei. After detailing the Sultan’s powers, contextualizing the monarchy’s stability, and introducing its state ideology, Melayu Islam Beraja (“MIB”), the article addresses formal laws, such as Brunei’s Constitution and a new Islamic penal code, which are symbolically significant for the MIB state’s (self-)legitimation but have little immediate relevance to many Bruneians’ lives. The article, therefore, shifts its focus to normative spheres that receive much less scholarly attention but, arguably, should—namely state-rituals like the Sultan’s three-week-long birthday celebrations. These, and other non-legal spheres, including, also, royal speeches, contain normative aspects that reflect and impact key developments in the MIB state. Grounded in the Royal Birthday’s and Islamic penal code’s analysis, the final part problematizes stereotypes of Brunei being a “sharia state” vis-à-vis its multidirectional normative messages and ability to hybridize broad cultural influences for the ruling system’s benefit.<br
Keywords: Brunei Darussalam; absolute monarchy; everyday state-making; Royal Birthday; Islamic law

Brunei in 2015: Oil revenues down, Sharia on the rise - Mueller, Dominik M. (Asian Survey, 2016)
The oil price decline of 2015 caused significant losses for Brunei's economy. The country is still preparing the second phase of its Sharia reform that began in 2014. In addition to his other government positions, Sultan Hassanal Bolkiah appointed himself as minister of foreign affairs and trade, replacing Prince Mohamed Bolkiah.
Created from Fastlane, Scopus look-up
Keywords: Brunei; Fighting corruption; Oil price crisis; Sharia

Brunei’s Sharia Penal Code Order: Punitive Turn or the Art of Non-Punishment? - Müller, Dominik (Journal of Islamic Law, 2020)
In his essay, Dominik M. Müller takes an historical approach. He traces Brunei’s new Islamic criminal code back to the country’s independence in 1984, and even further, to the so-called Anglo-Mohammadan law established by the British protectorate earlier in the twentieth century, and to the Hukum Kanun Brunei before that—some version of which may have stretched all the way back to Islam’s arrival to Borneo in the fifteenth century. Müller is the first to assess the Code based on the evidence, albeit from Phase One. From 2014 to 2019, Phase One saw some application of the new Islamic Code to misdemeanors, but the degree paled in comparison with applications of the existing state Code. Looking at a twelve-month period from 2015 to 2016, Müller counts a total of 247 prosecutions under the new Code, all including fines (with the corporal punishments of the new code from Phases Two and Three not yet in effect). He puzzles over the expressions of surprise among the international media outlets at the new Code, given the long history that preceded as well as the legislative history that followed the phased introduction of the new law announced in 2013, and the minor penalties since. Müller then contrasts the international criticism with the local response: feeling under attack, an educated elite and other social media influencers in Brunei closed ranks in support of the new Code under the banner #BruneiUnited. For Müller, while none of these developments should have surprised the world, the fact that they did likely follows from the fact that Brunei is both historically relatively insular and the "academically most understudied Southeast Asian country." If true, his observation underscores the extent to which more research is required.<br

BUREAUCRATIC ISLAM COMPARED: CLASSIFICATORY POWER and STATE-IFIED RELIGIOUS MEANING-MAKING in BRUNEI and SINGAPORE - Mueller, Dominik M. (The Journal of Law and Religion, 2018)
This article presents a comparative anthropological approach to studying the bureaucratization of Islam in contemporary Southeast Asia. In line with this approach, the article understands the bureaucratization of Islam not simply as a formalization, expansion, and diversification of Islamic institutions and legal frameworks; rather, bureaucratization is investigated as a social phenomenon that transcends its organizational boundaries and informs dynamics of socio-legal change alongside transformations of the meaning(s) of Islam in state and society. The article centers the state's classificatory power and its societal coproduction and contestation, and it takes both functional and hermeneutic modes of analysis into consideration. While the bureaucratization of Islam is always embedded in and shaped by power-political constellations, it simultaneously produces social and doctrinal meanings that are unique to its locally specific discursive arenas. Therefore, more conventional functional perspectives on bureaucratic Islam can be beneficially enriched by a more hermeneutically oriented anthropological analysis, as the article illustrates, based on ethnographic data gathered in Brunei and Singapore. The article first introduces the anthropology of bureaucracy and elaborates on the absence of such studies on state-Islam relations in Southeast Asia, as well as the potential of bringing these streams of scholarship into a fruitful dialogue. Second, it presents the Bruneian case study, focusing on postcolonial Islamization policies, the bureaucratization of a national ideology, legal reforms, and their workings on the microlevel. Third, it moves on to a regional comparison, by illustrating how Islamic knowledge and meaning-production inherent to the bureaucratization of Islam unfolds quite differently in Singapore, despite partly overlapping functional patterns. While anchored in Brunei and Singapore, the article offers a conceptual framework and analytic vocabulary for a wider study across and potentially beyond the region.
Created from Fastlane, Scopus look-up
Keywords: Brunei; bureaucracy; classificatory power; Islam; law and social change; Singapore; Southeast Asia

Die staatliche Verfolgung von Magiern in Brunei Darussalam und Saudi-Arabien - Müller, Dominik; et al. (Normenkonflikte in pluralistischen Gesellschaften, 2017)

From Consultancy to Critique: The ‘Success Story’ of Globalized Zakat Management in Malaysia and its Normative Ambiguities - Mueller, Dominik M. (Globalizations, 2017)
The administration of Islamic alms (zakat) funds in Malaysia underwent spectacular transformations since the 1990s, shaped by the appropriation of marketized forms of management and a skyrocketing growth of collection and distribution rates. Simultaneously, local zakat funds are increasingly used to pursue targets of sustainable poverty reduction, such as the empowerment of micro-entrepreneurship. This globally inspired ‘success story’ is referred to by various international observers, including development organizations, as a ‘role model’ for other countries to learn from. After illustrating what makes the Malaysian case so particularly attractive, this article develops a critique of international perceptions of this ‘success story’ by making explicit some of its underlying ambiguities. Instead of narrowly celebrating instrumental aspects of business-style organizational innovation and calling for their globalization, a deeper understanding of the discursive embeddedness of Malaysian zakat management would reveal significant normative tensions with secular humanitarian ethics and human rights law, with implications beyond the Malaysian case.
Created from Fastlane, Scopus look-up
Keywords: development cooperation; human rights; humanitarianism; Islamic alms (zakat); Malaysia; religious marketization

"How Has the Islamic Party of Malaysia's Stance Towards Popular Culture Evolved?", Latest Thinking (Video) - Mueller, Dominik M.; et al. (2017)
While numerous studies on Islamic political movements are concerned with their engagement in party coalitions and the state, surprisingly few scholars have investigated the cultural life of Islamist groups. This article explores how the Islamic Party of Malaysia (PAS) is currently undergoing dramatic cultural changes and has developed an unprecedented flexibility in the field of modern popular culture. It elucidates how PAS has shifted from a group that long held the image of conservative zealots who try to ban any form of art and entertainment towards being a pioneer of pop-cultural creativity, as popular music, celebrity persons, and even motorbikes have been passionately integrated into its ‘Islamic struggle’. PAS' cultural transformation has not only been influenced by political competition and wider social tendencies, but also by the emergence of a new generation of cultural reformists within the party. Their call for change is driven by tactical considerations and reconsiders theological positions that stipulate that modern music is strictly forbidden in Islam. Electric guitars have thereby been re-conceptualised from ‘instruments of the devil’ to tools for missionary work (dakwah). The underlying process of normative change, however, continues to be highly controversial in the community of Malaysia's Islamist opposition.<br
Keywords: Islamism; popular culture; music; normativity; Parti Islam se-Malaysia (PAS); Malaysia

Hybride Wege zur Orthodoxie: Bürokratisierter Exorzismus, Scientization und die Neuerfindung deviant-erklärter übernatürlicher Praktiken in Brunei Darussalam - Müller, Dominik (Sprache | Macht | Magie, 2020)

Hybrid pathways to orthodoxy Bureaucratisation, Sharia-compliant exorcism and the powers of Japanese water-crystal photography in Brunei Darussalam - Müller, Dominik (Continuity and Change in Brunei Darussalam, 2021)
CRIS-Team WoS Importer:2022-09-02

Hybrid Pathways to Orthodoxy: Bureaucratisation, Sharia-Compliant Exorcism and the Powers of Japanese Water-Crystal Photography in Brunei Darussalam - Müller, Dominik (Continuity and Change in Brunei Darussalam, 2021)
Keywords: Brunei; Culture; Islam; Southeast Asia; Anthropology

Hybrid Pathways to Orthodoxy in Brunei Darussalam: Bureaucratised Exorcism, Scientisation and the Mainstreaming of Deviant-Declared Practices - Mueller, Dominik M. (Journal of Current Southeast Asian Affairs, 2018)
This article investigates the bureaucratisation of Islam in Brunei and its interlinkages with socio-cultural changes. It elucidates how realisations of state-enforced Islamic orthodoxy and purification produce locally unique meanings, while simultaneously reflecting much broader characteristics of the contemporary global condition. The article first introduces a theoretical perspective on the bureaucratisation of Islam as a social phenomenon that is intimately intertwined with the state's exercise of classificatory power and related popular processes of co-producing, and sometimes appropriating symbolic state power. Second, it outlines the historical trajectory of empowering Brunei's national ideology, Melayu Islam Beraja (MIB). It then explores social imaginaries and bureaucratic representations of “deviant”-declared practices, before illustrating how these practices become reinvented within the parameters of state power as “Sharia-compliant” services to the nation state. Simultaneously, national-religious protectionism is paradoxically expressed in thoroughly globalised terms and shaped by forces the state cannot (entirely) control. Newly established Sharia-serving practices become culturally re-embedded, while also flexibly drawing upon multiple transnational cultural registers. In the main ethnographic example, bureaucratised exorcism, Japanese water-crystal photography and scientisation fuse behind the “firewall” of MIB. These hybrid pathways to orthodoxy complicate the narratives through which they are commonly framed.<br
Keywords: Brunei; Islam and the State; Bureaucracy; classificatory power; exorcism; globalization

Islamic authority and the state in Brunei Darussalam - Müller, Dominik (2018)

ISLAMIC POLITICS AND POPULAR CULTURE IN MALAYSIA: Negotiating normative change between shariah law and electric guitars: COMMENDATION 2014 YOUNG SCHOLARS COMPETITION - Mueller, Dominik M. (Indonesia and the Malay World, 2015)
While numerous studies on Islamic political movements are concerned with their engagement in party coalitions and the state, surprisingly few scholars have investigated the cultural life of Islamist groups. This article explores how the Islamic Party of Malaysia (PAS) is currently undergoing dramatic cultural changes and has developed an unprecedented flexibility in the field of modern popular culture. It elucidates how PAS has shifted from a group that long held the image of conservative zealots who try to ban any form of art and entertainment towards being a pioneer of pop-cultural creativity, as popular music, celebrity persons, and even motorbikes have been passionately integrated into its ‘Islamic struggle’. PAS' cultural transformation has not only been influenced by political competition and wider social tendencies, but also by the emergence of a new generation of cultural reformists within the party. Their call for change is driven by tactical considerations and reconsiders theological positions that stipulate that modern music is strictly forbidden in Islam. Electric guitars have thereby been re-conceptualised from ‘instruments of the devil’ to tools for missionary work (dakwah). The underlying process of normative change, however, continues to be highly controversial in the community of Malaysia's Islamist opposition.
Created from Fastlane, Scopus look-up
Keywords: Islamism; Malaysia; music; normativity; Parti Islam se-Malaysia (PAS); popular culture

Islam, Law, and the State - Müller, Dominik (The Oxford Handbook of Law and Anthropology, 2020)
In the ever-growing corpus of anthropological scholarship addressing Islam and Muslim lifeworlds, comparably few studies centre on the intersections of Islam, law, and state power. This chapter begins with an introduction to some classical legal anthropological works that were influential in fields such as Islamic courtroom ethnography, disputing, and legal pluralism and that reflected on positivistic reconfigurations of the sharia caused by (post)colonial forces, most of which were not overly interested in the state as a core object of empirical and analytic enquiry. The chapter then shifts attention to more recent works that have opened up new directions and dealt increasingly with Islam’s intricate and contingent relationships with law, the state, and wider legal politics in specific contextual settings, factoring in overlapping sovereignties such as marketization in the religious and political field. These studies address, for example, the (trans)formation of sharia norms in corporate workplace settings, halal politics and related state-market dynamics, and the societal workings of state attempts to govern and bureaucratize Islam. They derive their strength from long-term ethnographic endeavours that follow social actors into spheres where they render the sharia meaningful, often in ways that would not immediately be associated with law or legal studies as a result of European-rooted secular distinctions. These and other emerging fields offer sociolegal scholars a range of timely and often understudied avenues for future research that could potentially hold significance for broad readerships within and beyond anthropology and sociolegal studies.<br
Keywords: Islam; sharia; Islamic law; everyday state-making; courtroom ethnography; halal

Islam, politics and youth in Malaysia: the pop-Islamist reinvention of PAS - Müller, Dominik (Routledge (Taylor & Francis), 2014)

Majlis Ugama Islam Singapura - Müller, Dominik (2020)

Malaysia - Müller, Dominik; Biro, Timea (Encyclopedia of Islam Three, 2021)
Keywords: Islam; Malaysia; Politics; Law; Southeast Asia

Malaysia. Sharia transformations: Cultural politics and the rebranding of an Islamic judiciary By Michael G. Peletz Oakland: University of California Press, 2020. Pp. 238. Maps, Table, Figures, Bibliography, Index. - Müller, Dominik M (Journal of Southeast Asian Studies, 2022)

Melayu Islam Beraja: Islam, Staat und politische Kommunikation in Brunei Darussalam. - Müller, Dominik (Islam und Staat in den Ländern Südostasiens . Islam and State in Southeast Asia, 2010)

Müller, Dominik. 2022. 10 questions for Dominik Müller. Interview by Stefan Schwendtner. The Alumni Interview. Halle/Saale: Max Planck Institute for Social Anthropology. https://www.eth.mpg.de/eth/en/newsarchiv/alumni-interview-mueller. Accessed May 17, 2022. - Müller, Dominik (2022)

Paradoxical normativities in Brunei Darussalam and Malaysia: Islamic law and the ASEAN Human Rights Declaration - Mueller, Dominik M. (Asian Survey, 2016)
Brunei and Malaysia are promoting the ASEAN Human Rights Declaration but enforce a brand of Islamic law that systematically violates it. The paradoxical ways in which policymakers are navigating between the two, and the empirical realities of Islamic governance, impede the project of a transdoctrinal justification of human rights.
Created from Fastlane, Scopus look-up
Keywords: ASEAN; Brunei darussalam; Human Rights; Islamic governance; Malaysia

Pluralism in Brunei’s Constitution? Ethnicity, Religion and the Absolute Monarchy - Steiner, Kerstin; Mueller, Dominik M. (Pluralist Constitutions in Southeast Asia, 2019)
This book examines the presence of ethnic, religious, political, and ideational pluralities in Southeast Asian societies and how their respective constitutions respond to these pluralities. Countries covered in this book are Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, and Vietnam. The chapters examine: first, the range of pluralist constitutional values and ideas embodied in the constitutions; secondly, the pluralist sources of constitutional norms; thirdly, the design of constitutional structures responding to various pluralities; and fourthly, the construction and interpretation of bills of rights in response to existing pluralities. The ‘pluralist constitution’ is thus one that recognises internal pluralities within society and makes arrangements to accommodate, rather than eliminate, these pluralities. <br

Post-Islamism or Pop-Islamism?: ethnographic observations of Muslim youth politics in Malaysia - Müller, Dominik (Paideuma: Mitteilungen zur Kulturkunde, 2013)

Redesigning Justice for Plural Societies - Alidadi, Katayoun; Foblets, Marie-Claire; Müller, Dominik (Routledge, 2022)
This volume examines cases of accommodation and recognition of minority practices: cultural, religious, ethnic, linguistic or otherwise, under state law. The collection presents selected situations and experiences from a variety of regions and from different legal traditions around the world in which diverse societal stakeholders and political actors have engaged in processes leading to the elaboration of creative, innovative and, to a certain extent, sustainable solutions via accommodative laws or practices. Representing multiple disciplines and methodologies and written by esteemed scholars, the work analyses the pitfalls and successes of such accommodative practices, presenting insights into how solutions could or could not be achieved. The chapters address the sustainability and transferability of such solutions in order to further the dialogue in both scholarly and policy spheres. The book will be essential reading for academics, researchers, and policy-makers in the areas of minority rights, legal anthropology, law and religion, legal philosophy, and law and migration.<br

Reviewed Work: Piety and Politics: Islamism in Contemporary Malaysia by Joseph Chinyong Liow - Müller, Dominik (South East Asia Research, 2010)

Rezension: "Schuckmann, Alewtina: Jugend und Gender in Marokko. Eine Ethnographie des urbanen Raums. Bielefeld: transcript, 2019." - Müller, Dominik (Anthropos, 2020)

'Save Gaza!‘: Reaktionen auf den Gaza-Konflikt im Diskurs der Islamischen Partei von Malaysia (PAS) - Müller, Dominik (2009)

Social categorization and religiously framed state-making in Brunei: from criminalizing supernatural healers to the rise of bureaucratized exorcism - Müller, Dominik (2018)

State-Islam relations in Southeast Asia: a comparative perspective - Müller, Dominik (Ethics, Politics and Law, 2018)

Taming the Wild: Aborigines and Racial Knowledge in Colonial Malaya - Mueller, Dominik M. (Asia Pacific Journal of Anthropology, 2017)

The bureaucratization of Islam and its socio-legal dimensions in Southeast Asia: conceptual contours of a research project - Müller, Dominik (2018)

The Shaping of Islam in Brunei Darussalam 1 - Müller, Dominik (Routledge Handbook of Islam in Southeast Asia, 2022)
This chapter discusses historical and contemporary developments of Islam in the sultanate of Brunei Darussalam, focusing on the transformations in the political position and social meanings of Islam in state and society. After a brief introduction of Islam in the pre-colonial period, the chapter outlines changes that occurred in the colonial era under British indirect rule, resulting in dramatic innovations pertaining to the administration and legalistic expression of Islam. New institutional and legal manifestations of Islam established during the colonial period structured later developments in the post-colonial era, beginning in 1984. The next section elucidates the rise of the post-colonial state’s national ideology called Melayu Islam Beraja, commonly referred to as ‘MIB’ and officially translated as ‘Malay Islamic Monarchy.' After a discussion of the contemporary ‘MIB State’ and government attempts of promoting the national ideology among its citizenry, the chapter turns to state attempts of supposedly ‘purifying’ Islamic practices and beliefs among the population, which have intensified since the 1990s, coinciding with significant sociocultural changes among the Malay majority population. Finally, the chapter offers concluding remarks on research gaps and potentials for future research.
CRIS-Team Scopus Importer:2022-10-28

The Shaping of Islam in Brunei Darussalam - Müller, Dominik (Routledge Handbook of Islam in Southeast Asia., 2022)

Transit ins Paradies: IS-Rekruten und das Problem ideologischer Terrorismusbekämpfung in Malaysia - Müller, Dominik (2015)

Ummah revisited: anti-Shia hatred in Malaysia since the outbreak of the Syrian civil war - Müller, Dominik (Illusions of democracy: Malaysian politics and people Volume II, 2019)

When ‘PAS is HAMAS’ and ‘UMNO acts like Israel’: localized appropriations of the Palestine conflict in Malaysia - Müller, Dominik (Graffiti, converts and vigilantes: Islam outside the mainstream in maritime Southeast Asia, 2015)